Migration of endothelial cells on the surface of anodized Ni-Ti stent strut - Wang, Zi; Ohtsu, Naofumi; Tate, Kasumi; Kojima, Yukiko; Saifurrahman, Hanif; Ohta, Makoto (Frontiers in Medical Technology, 2023)
Background Stent is widely regarded as the main treatment for curing cardiovascular diseases such as stenosis. Previous research has revealed that the damage of endothelial cells (EC), i.e., the components of endothelium, during stent implantation, could lead to severe complications, such as restenosis. To prevent restenosis, enhancements have been made to surface biocompatibility to accelerate the stent endothelialization process. Anodization on the Ni-Ti is a simple and efficient surface modification method to improve the biocompatibility of the Ni-Ti stent surfaces by enhancing the surface hydrophilicity, leading to an increase in the EC activities. The EC activity is known to be affected by the blood flow. Flow change by stent structure may result in EC dysfunctions, thereby leading to restenosis. It is thus essential to investigate the EC activities resulting from the anodization on the Ni-Ti surface under flow conditions. Objective To study the influence of the endothelialization process on the Ni-Ti stent surface through anodization. The EC attachment and morphology on the anodized stent strut were observed under both with and without the flow conditions. Method A parallel plate flow chamber was designed to generate a constant wall shear stress (WSS) to study the flow effect on the EC behavior. The hydrophilicity of the Ni-Ti stent strut surface was enhanced by a TiO2 layer fabricated via anodization. The EC distribution on the surface of the anodized nitinol stent strut was observed after 24 h of static (without flow) and flow exposure (with flow) experiment. Results Under the static condition, the EC density on the surface of the anodized Ni-Ti stent strut was higher compared with the control. Under the flow condition, the enhancement of the EC density on the surface of the stent strut with anodization was reduced. The EC demonstrates a long and thin spindle-shaped morphology under the flow condition. Conclusion Unlike the static condition, the EC is demonstrating a long and thin morphology in response to the flow under the flow condition. By improving the surface hydrophilicity, the anodization could enhance the EC migration onto the strut surface, and subsequently, accelerate the Ni-Ti stent endothelialization process. The improvement of the surface hydrophilicity is lower under the flow conditions when compared with the static conditions.